Local Wisdom Comics of Tuban District Culture: As a Media to Stimulate The Expressive Language of Early Children - Endang Puspitasari; Roudlotun Ni'mah (Journal of Islamic Education Students (JIES), 2024)
Language ability is one of the abilities that is being developed in early childhood, one of which is expressive language. The aim of this research is to analyze the application of comic media with local cultural wisdom in Tuban district in stimulating the expressive language of early childhood. This type of research is experimental research with a one group-pretest-posttest design. In the sampling technique, cluster sampling was used with a total research sample of 50 children. Data collection techniques using observation sheets, tests and documentation. The data analysis technique uses the Wilcoxon Test. The results of the Wilcoxon test research mean that the average rank between the pretest and posttest was 18.00, with a Z of -5.445 and a significance of 0.000 <0.05, indicating that the hypothesis was accepted that there was an influence on children's expressive language after being given story treatment using comic media, local cultural literacy in Tuban district had differences. which is significant.